The Implementation of Using Picture Media on Teaching Present Continuous Tense - Sari, Mezia Kemala; Putri, Yulyana (Universitas Negeri Semarang, 2018)
The research is about the implementation of using picture as the media in teaching Present Continuous tense. The purpose is to see is there any significant implementation of using media in teaching Present Continuous Tense. This research conducts three steps (pre-test, treatment and post-test) and held in four meetings. The participants are 21 students of class VIIA of MTs Muhammadiyah Padangpanjang by using purposive sampling. This pre-experimental research is quantitative and the data taken from pre-test and post-test and test sheet is used as the instrumentation. The result showed that the using of picture as media has implementation in teaching Present Continuous Tense. It can be seen from the student‘s scores‘ improvements taken from all indicators. Generally, total mean of students‘ score of pre-test is 43.24 meanwhile the mean score of post-test is 71.62. The effectiveness of using this media is implemented from students‘ scores which are increased after learning Present Continuous Tense by using picture. While the most significant improvement is in the use of –ing form as the core of the Present Continuous Tense.